The association of ABO and rhesus blood type with the risks of developing SARS-CoV-2 infection: a meta-analysis - Soo, K. M.; Chung, K. M.; M. A. A., Mohd Azlan; Lam, J. Y.; Ren, J. W. X.; Arvind, J. J.; Wong, Y. P.; Chee, H. Y.; Amin Nordin, Syafinaz (Malaysian Society of Parasitology and Tropical Medicine, 2022)
Coronavirus Disease 2019 (COVID-19) has been spreading like a wildfire everywhere in the globe. It has been challenging the global health care system ever since the end of 2019, with its virulence and pathogenicity. Recent studies have shown the association between ABO blood group, Rhesus blood type and susceptibility to COVID-19 infection. Various studies and few meta-analyses have been done and some might be inconsistent; therefore, this meta-analysis was done to assess the relationship between different ABO and Rhesus blood types on the susceptibility to COVID-19 infections. This meta-analysis assessed the odds ratio of COVID-19 infection of different ABO and Rhesus blood types. Subgroup analyses according to (1) age and gender matched; (2) different blood group antigens; (3) Rhesus positive and negative of each blood group were carried out. Publication bias and Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) were also done to assess the risk of bias in these publications. It was found that blood group A showed significant difference in odds ratio of COVID-19 infection (OR, 1.16; 95% CI, 1.08-1.24). Blood group AB showed significant difference in odds ratio when studies with lower QUADAS-2 score were removed. This means that populations with blood group A and AB are more likely to be infected with COVID-19. As there is a higher tendency that blood group A and AB to be infected with COVID- 19, precautious care should be taken by these populations.